Subjective life satisfaction among urban malay civil servants : the case of administrative staff of the University Technology MARA Malaysia (UiTM), Shah Alam - Nor Hafizah binti Mohamed Harith (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2014)
Empirical data for the measure of quality of life in Malaysia has largely employed objective indicators (MQLI, 2004) and are used mainly in quantitative research. This situation has left research on subjective life satisfaction or well-being largely unexplored or limited. In light of the above, one may ask: if the MQLI has shown high score on the objective indicators, how far does this score reflect upon the people's subjective life satisfaction. Adopting a case study design, this study focuses on exploring subjective life satisfaction among urban Malay civil servants in Malaysia. Being qualitative in nature, the research is concerned mainly with the emic than the etic views and perspectives (Merriam, 2009). Framed within a modified Allardt's theory of need and MQLI, the study among others explores the factors that contribute to the life satisfaction among staff members of a Malaysian public university namely Universiti Teknologi MARA or UiTM. Sixteen respondents from four different categories of the University's administrative staff working at its main campus in Shah Alam, Selangor were engaged in the research. Data collected via indepth interviews were later verified through Written Feedback Validation (WFV) form. The main findings have shown that: 1) Most respondents were satisfied with their life with moderation being the major theme revealed, 2) The factors that determine the subjective life satisfaction were centered around three major themes namely; a) satisfying living condition needs, b) satisfying non-living condition needs and c) satisfying spiritual comfort need, with the last two being the main priority of the respondents. 3) The meaning of life satisfaction among the respondents was centered around three major themes; the need for spiritual development, the need for economic satisfaction and the social needs with the economic need being the main concern of the lower and middle class participants. 4) In general, gender, social class and working experiences have no significant bearing upon respondents' satisfaction. Nonetheless, the findings have revealed that most female respondents perceived their working life to be a factor that enhanced their SWB. In addition, respondents of different social class showed slightly different coping ability to cope with urban life. These findings have significant bearing upon development policy in Malaysia.